ANALISIS KINERJA KEUANGAN PERUSAHAAN YANG TERGABUNG DALAM INDEKS SAHAM SYARIAH INDONESIA (ISSI) YANG MELAKULAN STOCK SPLIT TERHADAP RETURN SAHAM - Permatasari, Maharani; Isnaini, Desi; Setiawan, Evan (JURNAL ILMIAH EDUNOMIKA, 2024)
This research aims to test whether there is an influence of Return on Assets (ROA), Total Assets Turnover (TATO), Earning Per Share (EPS) and Price Earning Ratio (PER) on Stock Return with a total sample of 7 companies that carry out stock splits which are members of Indonesian sharia stock index (ISSI) in the 2019-2022 period. Research data was collected using documentatiom and library methods and analyzed using multiple linear regression. The results of the F hypothesis test research show a sig value of 0,773 > 0,05, so it can be caonclude that Return on Assets (ROA), Total Assets Turnover (TATO), Earning Per Share (EPS) and Price Earning Ratio (PER) do not have an effect together as stock returns. The t test results show a sig value of ROA 0,934, TATO 0,386, EPS 0,407 and PER 0,659 where the sig value of all variables is greater than 0,05 so it can be conclude that Return on Assets (ROA), Total Assets Turnover (TATO), Earning Per Share (EPS) and Price Earning Ratio (PER) have no partial effect on stock returns.